2013
DOI: 10.1007/s00415-013-7143-4
|View full text |Cite
|
Sign up to set email alerts
|

Papilloedema is an independent prognostic factor for POEMS syndrome

Abstract: POEMS syndrome is a potentially fatal disease, and prediction of prognostic factors for POEMS syndrome is important for clinicians. Papilloedema is an early sign of the syndrome. The present study was carried out to evaluate whether papilloedema is a prognostic factor for POEMS syndrome. Between January 2003 and December 2012, 94 patients with POEMS syndrome were enrolled in this study. The patients were divided into groups with and without papilloedema. Logistic regression was performed to identify risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 23 publications
4
35
1
1
Order By: Relevance
“…ODO was detected bilaterally in 13 patients (76%), which is consistent with earlier reports that bilateral ODO was the most common (30%–70%) sign in POEMS syndrome 1 4 6 8 11. The cause of the ODO in POEMS syndrome has not been determined, but it has been suggested that an elevated ICP,7–9 11 vasculitis,18 presence of cerebrospinal fluid proteins,11 infiltrations into the optic nerve,19 or increased VEGF levels4 8 10 20 may be involved.…”
Section: Discussionsupporting
confidence: 91%
“…ODO was detected bilaterally in 13 patients (76%), which is consistent with earlier reports that bilateral ODO was the most common (30%–70%) sign in POEMS syndrome 1 4 6 8 11. The cause of the ODO in POEMS syndrome has not been determined, but it has been suggested that an elevated ICP,7–9 11 vasculitis,18 presence of cerebrospinal fluid proteins,11 infiltrations into the optic nerve,19 or increased VEGF levels4 8 10 20 may be involved.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is unsurprising that most previous studies concentrated on the survival value of a single clinical variable [5,6,24,25]. A critical question always asked by physicians caring 9 for such patients is the risk factors that could predict overall survival independently.…”
Section: Discussionmentioning
confidence: 96%
“…The most common ocular symptoms reported were blurred vision in 15, diplopia in 5, and ocular pain in 3. In another series of 94 patients, papilledema, which was found in 50% of patients, was an adverse prognostic feature for overall survival [53].…”
Section: Diagnosismentioning
confidence: 89%
“…Whether the digital clubbing seen in POEMS is a reflection of underlying pulmonary hypertension and/or parenchymal disease is yet to be determined. Impaired DLCO has been shown to be an adverse prognostic factor in another series [53]. The histologic findings of the dermis have been reported to range from non-specific to glomeruloid hemangiomata to vascular abnormalities in apparently normal dermis [81][82][83].…”
Section: Diagnosismentioning
confidence: 99%